Designing a Teaching Pattern from Students’ Lived Experiences of the Teaching Process in Universities of Iran (Technical and Engineering Disciplines) - Turki Nisiani, Batul; Keshtiaray, Narges; Sharifian, Farzad (Iranian Journal of Educational Sociology, 2022)
Purpose: The present research aimed to designing a teaching pattern from students’ lived experiences of the teaching process in universities of Iran in technical and engineering disciplines.Methodology: This study in terms of purpose was applied and in terms of implementation was qualitative from type of phenomenological. The study population consisted of postgraduate and PhD students in technical and engineering disciplines of Australian universities (Melbourne, Monash and Swinburne) in 2018 year who had the experience of studying at the undergraduate and graduate levels in Iran country. The research sample according to the theoretical saturation principle was determined 10 people who were selected by purposive sampling method. Data were collected through semi-structured depth interview method which its validity was confirmed by the method of reconstruction of reality and its reliability was confirmed by conducting interviews in a quiet and unbiased atmosphere and to analyze data used from thematic coding method.Findings: Findings showed that students’ lived experiences of the teaching process in Iranian universities in technical and engineering fields had 197 initial concepts and 38 final concepts in 3 main components: professor (23 concepts), student (7 concepts) and content (8 concepts). Also, based on the concepts and components derived from the students’ lived experiences of the teaching process, the teaching model in technical and professional fields was designed and approved based on the opinion of experts.Conclusion: According to the results, planners and officials to design curriculum and professors to improve their teaching can use the teaching model designed in this research to improve the quality of education in universities.